Inactivation of Thrombin by the Aortic Endothelium - Swedenborg, J; Dryjski, M; Olsson, P (Thrombosis and Haemostasis, 1983)
The aim of the investigation was to clarify the uptake of thrombin on vascular endothelium and the inhibition of thrombin on the endothelium in the presence or absence of plasma. Segments of porcine aorta were used. Thrombin was labelled with 125I and its enzymatic activity was assayed amidolytically using a specific chromogenic substrate. After exposure to the endothelium both enzymatic activity and radioactivity disappeared from the thrombin solution and were recovered as surface bound activities.The enzyme activity confined to the endothelium rapidly disappeared in the presence of plasma but no activity was recovered in the plasma. The surface confined radioactivity, however, decreased slowly and was quantitatively recovered in the plasma. In the absence of plasma, i. e. in the presence of a balanced Ringer’s solution, only slow disappearance of thrombin enzymatic activity occurred although the rate of disappearance was higher than that of release of radioactivity.It is concluded that thrombin, taken up on the endothelium, is almost instantaneously inhibited by an interaction mechanism with plasma and then released in an inactive state. The endothelium itself, however, seems to slowly inhibit bound thrombin and then release it.
Keywords: Endothelium; Thrombin; Inhibition